EU and Mercosur in the twenty-first century: Taking stock of the economic and cultural ties - Oscar Guinea; Vanika Sharma (European Centre for International Political Economy (ECIPE), 2021)
This policy brief examines the latest developments in the EU-Mercosur economic relationship and outlines the existing non-economic relationship in order to contextualise the EU-Mercosur Association Agreement and its potential for strengthening common bonds between both regions.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Internationale Beziehungen; Außenhandel; Auslandsinvestition; Mercosur-Staaten; EU-Staaten